Recycled Aluminium Composite Pulley - Mazlee, Mohd. Noor; Shamsul Baharin, Jamaludin, Prof. Dr.; Murizam, Darus (International Exhibition of Inventions, 2010)
Mazlee Mohd Noor and his team won bronze at 34th International Exhibition of Inventions of Geneva organized by International Exhibition of Inventions on 18th - 22nd April 2007 at Palexpo Hall 7, Geneva, Switzerland.